2018
DOI: 10.12659/msm.911902
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Exerts an Anti-Epilepticus Effect, Possibly by Regulating the Nrf2-Keap1-ARE Signaling Pathway

Abstract: BackgroundStatus epilepticus (SE) is a refractory neurological disease with high mortality and morbidity rates. SE can be induced by numerous factors, including oxidative stress. Catalpol has several biological activities, including regulating the oxidative stress response. However, the role of catapol in SE has not been fully elucidated.Material/MethodsThirty Wistar rats were randomly and equally divided into 3 groups: a control group, an SE group established by LiCl-pilocarpine intraperitoneal injection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…CAT simultaneously, as a major component of RG, has been reported to display neuroprotective and antiapoptotic effects (Liang et al, 2009;Cai et al, 2011;Liu et al, 2014). In addition, CAT has been found to have anti-inflammatory and neuroprotective roles in inflammation-mediated Parkinson's disease, which can reduce neuronal degeneration caused by inflammation-triggered oxidative stress and ER stress (Liu et al, 2014;Xiong et al, 2017;Gao et al, 2018). CAT was also reported to protect podocytes in diabetic nephropathy via inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CAT simultaneously, as a major component of RG, has been reported to display neuroprotective and antiapoptotic effects (Liang et al, 2009;Cai et al, 2011;Liu et al, 2014). In addition, CAT has been found to have anti-inflammatory and neuroprotective roles in inflammation-mediated Parkinson's disease, which can reduce neuronal degeneration caused by inflammation-triggered oxidative stress and ER stress (Liu et al, 2014;Xiong et al, 2017;Gao et al, 2018). CAT was also reported to protect podocytes in diabetic nephropathy via inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these all results, it can be suggested that the anticonvulsant properties of catalpol and mannitol might be mediated by other pathways as well as GABAA receptor activities. For example, Gao et al (2018) reported that catalpol decreased LiCl/pilocarpine-induced seizure responses and altered Nrf2-Keap1-ARE expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several RG components, including aucubin, acteoside, catalpol, and mannitol, were screened to determine whether they have anticonvulsant effects, and catalpol, mannitol, and their combination were chosen for further assessment. Recently, using LiCl/pilocarpine, electroencephalography (EEG), or extracellular field recording in brain slice, some studies have reported that catalpol or mannitol might have anticonvulsant effects (Haglund and Hochman, 2005;Serafini, 2017;Gao et al, 2018), however, their roles remain unclear. In this study, their protective effects as well as that of their combination against electroshock-or chemically (PTZ or strychnine)-induced seizures, were evaluated in mice.…”
mentioning
confidence: 99%
“…Models of stress-induced depression showed that Nfr2 and HO-1 are downregulated, but catalpol (10 mg/kg) was shown to restore their levels and may target depression via the PI3K/Akt/Nrf2/HO-1 signaling pathway [ 100 ]. Studies on hyperglycemia-induced depression showed that catalpol (5, 10, and 20 mg/kg) reversed pathological phosphorylation of PI3K and Akt and restored Nrf2 and HO-1 levels, attributed to the upregulation of the PI3K/Akt/Nrf2/HO-1 signaling pathway [ 101 ].…”
Section: Terpenoidsmentioning
confidence: 99%